COMPLIANCE OF NATIONAL LEGAL QUALITY LEVEL, TRANSPORT AND TRANSPORTATION SERVICES SAFETY WITH WORLD STANDARDS IN PERSPECTIVE - Sarsembayev, Marat; Sarsembayev, Daniyar; Kussainova, Aiman; Nazarkulova, Lazzat (Journal of Applied Engineering Science, 2020)
In this article, the authors analyze the correspondence of international transport law and national (Kazakhstan) law on issues of ensuring the quality and safety of all types of transport and their transportation services. The article suggests the titles of a number of new international conventions and agreement son the need to implement the principles of quality, reliability, and safety of manufactured vehicles, as well a son the necessity to comply with transport safety rules during its operation, which must be developed and adopted in the future. Kazakhstan scientists, vehicle manufacturers must invent and produce original and at the same time reliable, efficient vehicles. Drivers of Kazakhstan’s vehicles, as well as drivers in all other countries, are required to follow traffic regulations related not to only modern cars, but also be able to drive future digitalized unmanned vehicles, all those types of transport that will run on solar and other energy of the future. In this regard, the authors proposed the titles of a number of domestic laws on the feasibility of creating new vehicles with high-quality, environmentally friendly engines, artificial intelligence-based steering, and a reliable chassis, which will be adopted in the legal field of Kazakhstan and other states. According to the authors of the article, such approaches will allow the quality and safety of transport and transportation in Kazakhstan to comply with international standards.